Konsep Pendidikan Prenatal dalam Perspektif Tafsir Al-Mishbāh Karya M. Quraish Shihab - Anwar Mujahidin; Zamzam Farrihatul Khoiriyah (Institut Agama Islam Negeri (IAIN) Tulungagung, 2018)
This study aims to analyze the tafseer al-Mishbāh by M. Quraish Shihab on the verses relating to the process of the human creation that has relevance to the concept of prenatal education. The approach used in this research is tafsir maudhū'i, ie tracing the verses relating to the problem under study and then described the interpretation of the verses. The data that have been collected then analyzed by the method of content analysis which analyze the interpreter's thoughts with theoretical categories so that found the main message and the context. The results of the study show that, God created the first human Adam and Eve then cultivate it into human offspring, by creating the womb. The stages of human development in the womb are ranging from nuthfah, 'alaqah, mudghah and ansya'a khalqan ākhar. The stage of ansya'a khalqan ākhar is the stage of the blowing of the spirit, the covenant of God with man, and God gives nature to man. Since that phase, children can get education. The effort to be done by parents in educating children in the prenatal period are running worship, reading and memorizing Al-Qur`a, dzikir, dialogue, follow the study of Islam (majlis ta`lim), behave well, and be consistent.